Hadith #5406 - Sahih Muslim - Abu Bashir Al-Ansari (Sahih Muslim)
I think he said (these words) when the people were at the places of rest: No necklace of strings be left on the necks of the camels or the necklace kept unbroken. Imam Malik said: To my mind (this practice) of wearing necklace round the necks of camels or animals was because of the fact that they (wanted to save them) from the influence of the evil eye.
Grade: Sahih